Adjuvant endocrine therapy in women with oestrogen‐receptor‐positive breast cancer: how should the skeletal and vascular side effects be assessed and managed?. (1st September 2016) - Ramchand, Sabashini K.; Lim, Elgene; Grossmann, Mathis
Summary: Adjuvant endocrine therapy provides oncological benefits in women with early oestrogen‐receptor‐positive breast cancer, but has adverse effects consequent to induced oestradiol deficiency. Bone loss is accelerated, predisposing to increased fracture risk. Metabolic effects include changes in lipid metabolism and body composition although effects on cardiovascular risk are still unclear. Women commencing endocrine therapy should be proactively counselled about and monitored for these and other therapy‐related complications including arthralgia and vasomotor symptoms. We provide strategies for prevention and management of these adverse effects, based, where available, on randomized controlled trial evidence specific to breast cancer survivors receiving endocrine treatment.